Assessment of the interaction of age and sex on 90-day outcome after intracerebral hemorrhage. (5th September 2017) - James, Michael L.; Langefeld, Carl D.; Sekar, Padmini; Moomaw, Charles J.; Elkind, Mitchell S.V.; Worrall, Bradford B.; Sheth, Kevin N.; Martini, Sharyl R.; Osborne, Jennifer; Woo, Daniel
Abstract : Objective: Because age affects hormonal production differently in women compared with men, we sought to define sex and age interactions across a multiracial/ethnic population after intracerebral hemorrhage (ICH) to uncover evidence that loss of gonadal hormone production would result in loss of the known neuroprotective effects of gonadal hormones. Methods: Clinical and radiographic data from participants in the Ethnic/Racial Variations of Intracerebral Hemorrhage study and the Genetic and Environmental Risk Factors for Hemorrhagic Stroke study prior to December 2013 were used. Relationships among sex, age, and outcome after ICH in 616 non-Hispanic black, 590 Hispanic, and 868 non-Hispanic white participants were evaluated using multivariable logistic regression analysis. Poor outcome was defined as modified Rankin Scale score ≥3 at 90 days after ICH. Results: Sex differences were found in multiple variables among the racial/ethnic groups, including age at onset, premorbid neurologic status, and neurologic outcome after ICH. Overall, no sex–age interaction effect was found for mortality ( p = 0.183) or modified Rankin Scale score ( p = 0.378) at 90 days after ICH. In racial/ethnic subgroups, only the non-Hispanic black cohort provided possible evidence of a sex–age interaction on 90-day modified Rankin Scale score ( p = 0.003). Conclusion: Unlike in ischemic stroke, there was no evidence that patient sex modified the effect of age on 90-day outcomes after ICH in a large multiracial/ethnic population. Future studies should evaluate biological reasons for these differences between stroke subtypes. Clinicaltrials.gov identifier: NCT01202864.